Implemetasi Penggunaan Software AutoDesk Inventor Dalam Meningkatkan Kompetensi Menggambar Teknik pada Pelajar Kejuruan. - Alviani Hesthi Permata Ningtyas (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
Improving the quality of human resources in the field of vocational education becomes the focus of goals in this community service activity. Through the training of software inventors, the quality of human resources in vocational schools SMK Muhammadiyah 1 Gresik, SMK KAL 1 Surabaya, SMK Maskumambang 1 and SMK PGRI 1 Gresik given understanding and knowledge about software Inventor that 73% of participants have never known the software before. With lecture methods, Q&A, demonstrations, and practices are given in the presentation of the material. The results of this software inventor training obtained a satisfaction score of 60% with a good assessment scale for facilitators, 53% for facilities and 53% for presenters, and 67% for materials provided. Suggestions for future training can be held with a longer duration and participants get an alloy book.